Analisis Komparatif Antara Hukum Nasional dan Hukum Islam - Ashfiya Nur Atqiya; Ahmad Muhamad Musta'in Nasoha; Aulia Nafiul Khoiriyah; Affan Tafta Naufalianto; Furqon Abdul Hakim (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This study aims to conduct a comparative analysis between national law and Islamic law, focusing on the principles, implementation, as well as the differences and similarities between the two in social, political, and cultural contexts. National law in Indonesia is a combination of customary law, colonial law, and modern law derived from Western legal systems, while Islamic law originates from Sharia, based on the Qur'an and Hadith. In certain areas, such as family law, civil law, and criminal law, these two legal systems exhibit distinct approaches, both philosophically and technically. The study finds that while national law emphasizes secularism and state sovereignty, Islamic law places greater emphasis on moral and divine justice. However, in the Indonesian context, both legal systems sometimes operate in parallel or undergo processes of adaptation and accommodation. This research contributes to a deeper understanding of the dynamics of the interaction between national law and Islamic law, as well as how both influence the judiciary and society in general.